Pengaruh Technological Pedagogical Knowledge (TPK) Guru Terhadap Pembelajaran Daring Di SD Budi Luhur Karang Tengah - Wahyu Ainun Habibah; Ainur Rosyid (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to determine the effect of teacher TPK variables on online learning at SD Budi Luhur. This research method uses a quantitative approach with a survey method. The data collection technique used a questionnaire with saturated sampling, with a sample size of 30 teachers. The calculation results obtained  of 0.958 with a partial test (t test) obtained t count = 2.128> t table = 2.048 with a significance of 0.000 <0.05, meaning that  is rejected and  is accepted with a correlation coefficient of 42.6% indicating that the TPK of the teacher contributes to Online learning is high and the coefficient of determination is 43%, the remaining 57% is influenced by other factors. Based on these data, it means that there is a positive and significant relationship with the TPK teacher variable with online learning variables